A study of resistance to airflow through grains - Reyes, Vicente Geronimo, Jr.; Jindal, Vinod Kumar; Kim, Kong-Hwan; Gupta, Ashim Das; Jensen, Jens Raunso; Government of Japan (Bangkok : Asian Institute of Technology, 1983)
In this study , the pressure gradient versus air velocity relation ships for various grains were investigated. The experimental grains had relatively uniform size distributions. The physical characteristics of grains including the volume, surface area and porosity were also determined using special techniques specifically developed for this study. The experimental data on resistance to airflow for all grains could be adequately represented by the quadratic, cublic and log-quadratic equations. The parameters of quadratic equations were distinctly related with the physical properties of grains and the air. However, this resulted into a poor prediction of pressure gradient versus air velocity relationships for about half of the grains. A general expression for calculating the pressure drop in bed of grains due to airflow and two dimensionless parameters characterizing the flow through such porous media were developed. A unique relationship was shown to exist between the modified friction factor and Reynold's number values for all grains considered in this study. Finally, it was shown that the proposed general equation can be used satisfactorily to predict pressure drop for a given bed of grain provided the porosity and volume to surface area ratio of the individual grains were known.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Grain aeration